Effect of "live high - train low" on EPO and acid-base balance - Townsend, N. E.; Gore, C. J.; Boston, T.; Emslie, K.; Hahn, A. G. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
It is generally thought that altitude exposure decreases arterial oxygen saturation (%SaO2) which stimulates an increase in EPO formation, resulting in an increase in red cell mass and VO2max. However, an increase in resting ventilation (VE) is one of the earliest responses to a reduced partial pressure of O2, which can lead to a decrease in arterial pCO2 and an increase in pH. Also, a significant inverse relationship between the decline in %SaO2 during sleep at 5,360m and the sea level hypoxic ventilatory response has been found (Masuyama et al., Jpn J Physiol, 39(4):523-35, 1989). Therefore, it was hypothesised that during sleep at altitude there would be a significant relationship between %SaO2 and blood acid-base balance. Thirteen male endurance athletes participated in the study. Six subjects (HIGH) spent 8-10 hr.night-1 for 23 nights at 3000m simulated altitude (normobaric hypoxia), whilst seven control (LOW) subjects slept at 600m. During sleep, pulse oximetry haemoglobin saturation (%SpO2) was monitored continuously in the HIGH group. Morning venous blood was collected one day prior to altitude and after 3, 5, 14, and 21 nights in both groups, and analysed for pH, pCO2, and [HCO3-]. Serum [EPO] was determined in the HIGH group only. A mean value for each acid-base variable was determined from the four blood samples taken during altitude exposure and the difference between this value and the pre-altitude data was calculated. Peak [EPO] was the highest value measured after night 3 or 5. Student t-tests were used to compare HIGH and LOW groups, and correlations were conducted to identify significant relationships between variables for the HIGH group. [EPO] increased in the HIGH group (8.99± 3.16 to 12.90± 5.88 mU.L-1), but not significantly (P=0.09). Change (D ) in pH and pCO2 was significantly greater in the HIGH (D pH=0.04± 0.03 units, P=0.01; D pCO2=-6.5± 4.0 mmHg, P=0.01) compared to the LOW (D pH=0.00± 0.02 units; D pCO2=0.0± 3.5 mmHg) group. The correlation (N=6) between sleeping %SpO2 and morning D [HCO3-] (r=-0.75, P=0.09), between %SpO2 and D pCO2 (r=-0.49, P=0.32), and that between %SpO2 and D pH (r=0.20, P=0.70) each failed to reach significance. However, a significant inverse relationship (r=-0.81, P=0.05) between D pH and D pCO2 was observed. The relationship between %SpO2 and D [EPO] was not significant (r=-0.34, P=0.52). The data suggest that "live high-train low" increases [EPO], but this change is not related to %SpO2. However, %SpO2 during sleep at altitude may be related to a chronic change in the acid-base balance of blood, secondary to increased VE. The possibility that mechanisms other than an increase in [EPO] could lead to performance enhancement following altitude acclimatisation should not be discounted.